2020
DOI: 10.1371/journal.pone.0231891
|View full text |Cite
|
Sign up to set email alerts
|

Hypomorphic SI genetic variants are associated with childhood chronic loose stools

Abstract: ObjectiveThe SI gene encodes the sucrase-isomaltase enzyme, a disaccharidase expressed in the intestinal brush border. Hypomorphic SI variants cause recessive congenital sucrase-isomaltase deficiency (CSID) and related gastrointestinal (GI) symptoms. Among children presenting with chronic, idiopathic loose stools, we assessed the prevalence of CSIDassociated SI variants relative to the general population and the relative GI symptom burden associated with SI genotype within the study population. MethodsA prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Cases of adult CSID misdiagnosed as IBS have been reported in the literature [45][46][47] , and retrospective analyses of multiple case-control cohorts from tertiary centres have demonstrated that SI functional polymorphisms predispose to IBS 48 . Thus, several rare and one common (Phe15Val) SI variant with reduced disaccharidase activity (hypomorphic variants, demonstrated in vitro) confer an increased risk of IBS [48][49][50][51] . Preliminary analyses from the same studies have also suggested that the interaction between SI genotype, gut microbiota and dietary carbohydrates might be important in determining IBS risk in exposed individuals 49 .…”
Section: Biobanksmentioning
confidence: 99%
“…Cases of adult CSID misdiagnosed as IBS have been reported in the literature [45][46][47] , and retrospective analyses of multiple case-control cohorts from tertiary centres have demonstrated that SI functional polymorphisms predispose to IBS 48 . Thus, several rare and one common (Phe15Val) SI variant with reduced disaccharidase activity (hypomorphic variants, demonstrated in vitro) confer an increased risk of IBS [48][49][50][51] . Preliminary analyses from the same studies have also suggested that the interaction between SI genotype, gut microbiota and dietary carbohydrates might be important in determining IBS risk in exposed individuals 49 .…”
Section: Biobanksmentioning
confidence: 99%
“…The pediatric pain-predominant DGBIs affect approximately 13.5%-15.8% of children worldwide (3,54,55). There are several inter-related factors playing a role in an individual, including psychosocial distress, visceral hypersensitivity, gut microbiome, and diet (3,6,(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70). Diet is an important perceived inducer of gastrointestinal symptoms in children with DGBIs, and 92%-93% of those with irritable bowel syndrome identify at least 1 type of food trigger which exacerbates their symptoms (57,58) and a higher median number of foods causing gastrointestinal symptoms (58,59).…”
Section: Pain-predominant Disorders Of Gut-brain Interactionmentioning
confidence: 99%
“…However, we speculate that a subset of fructan‐tolerant subjects (particularly those with the greatest increase in pain in response to maltodextrin) may have impaired starch digestion. In healthy individuals, including preterm infants, 53 maltodextrin is rapidly digested (see review by Hofman et al) 54 However, recently, it has been suggested that some individuals with symptoms of IBS have genetic variants associated with a reduction in sucrase‐isomaltase activity and subsequent impairment in sucrose and starch (ie maltodextrin) absorption leading to abdominal pain 55‐57 . Evidence suggests these variants may account for poor response to a low FODMAP diet in IBS 58 .…”
Section: Discussionmentioning
confidence: 99%